Surface nanopatterning of hard and soft thin films by a replica-molding approach - Vázquez, Luis (2004)
In this work, we report on our recent results obtained by a replica-molding approach for large-scale surface nanopatterning. Two materials with quite different mechanical properties have been naopatterned, namely: titanium nitride (TiN) films deposited by reactive sputtering and polystyrene films deposited by the casting procedure. In order to explore the capabilities of this strategy we have used in both cases as master surfaces to be replicated silicon surfaces previously nanostructured by low-energy ion-beam sputtering. The original template pattern was formed by an array of silicon lenticular nanodots, 6 nm of average height and 40-50 nm of lateral size, displaying short-range hexagonal order.